DERMATOLOGICAL CONDITIONS IN TRANSGENDER PATIENTS: A SYSTEMATIC REVIEW - Magdalena Domisiewicz,; Kacper Domisiewicz, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Transgender and gender-diverse (TGD) individuals face unique dermatological challenges, strongly influenced by gender-affirming hormone therapy (GAHT), surgical practices, and psychosocial determinants of health. Acne, androgenetic alopecia, hidradenitis suppurativa, infectious dermatoses, and the need for hair removal procedures represent the most prevalent conditions. Beyond clinical impact, these conditions affect social functioning, stigma, and access to equitable healthcare.Aim: To systematically review dermatological conditions in transgender patients, integrating clinical specificity with social science perspectives.Methods: A PRISMA-guided systematic review was conducted using PubMed through 2025. Inclusion criteria: studies reporting dermatologic conditions in transgender individuals. Exclusion: non-dermatology-focused papers. Eighteen studies (PMIDs 38086516–32115126) were included. Data on incidence, pathophysiology, treatment, and social determinants of care were extracted.Results: Testosterone therapy induced acne in 25–88% of transgender men, peaking within 6–12 months, with nodulocystic acne in up to 20%. Alopecia occurred after >2 years GAHT, mediated by dihydrotestosterone. Hidradenitis suppurativa was exacerbated by androgen exposure, with adalimumab effective in severe cases. Hair removal (laser, electrolysis) is essential pre-vaginoplasty but associated with folliculitis, scarring, and inequitable access. Transgender women demonstrated high prevalence of HPV/HIV-related dermatoses, with HIV prevalence up to 40% in some cohorts. Melanoma cases under estrogen therapy were reported, though causality remains uncertain. Psychodermatologic burden was severe, with depression affecting 40–50% of patients with visible skin disease.Conclusion: Dermatologic care in TGD patients is medically complex and socially contextual. Interventions must integrate pathophysiologic understanding with stigma reduction, insurance coverage, and equity-focused health policy.